SPECIFIC DIFFICULTIES IN LEARNING AMONG STUDENTS - DYSLEXIA (Annual of the Faculty of Philosophy in Skopje, 2016)
Dyslexia is topic for discussion which last for decades and furthermore is subject for itself British Association for Dyslexia give the best definition for dyslexia as combination of abilities and difficulties which affects on reading process, spelling and writing. In association are weakness as processing the information, short-term memory, concentration, sequencing, and organization, audit and/or visual perception, speech language and motor skills.In our country, in 2015, Macedonian Association for Dyslexia „Einstein“ conducted testing on 782 students, from two secondary schools in Skopje. The test for student A self estimation of dyslexia was taken over from the authors Kavkler, Magajana, Koshak- Baduer, Janzelj, Andrichek and Zemjak. The obtained data shows that approximately 10% of the students manifest signs of dyslexia. This information leads us to invest more forces in the field of dyslexia, in order to facilitate the learning dijficulties of students with dyslexia in our country.
Keywords: DIFFICULTIES IN LEARNING; DYSLEXIA; STUDENTS